Evaluation of an experimental rat model for comparative studies of bleaching agents - Cintra, Luciano Tavares Angelo [UNESP]; Benetti, Francine [UNESP]; Ferreira, Luciana Louzada [UNESP]; Rahal, Vanessa [UNESP]; Ervolino, Edilson [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Gomes Filho, João Eduardo [UNESP]; Briso, André Luiz Fraga [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2016)
Dental materials in general are tested in different animal models prior to the clinical use in humans, except for bleaching agents. Objectives: To evaluate an experimental rat model for comparative studies of bleaching agents, by investigating the influence of different concentrations and application times of H2O2 gel in the pulp tissue during in-office bleaching of rats' vital teeth. Material and Methods: The right and left maxillary molars of 50 Wistar rats were bleached with 20% and 35% H2O2 gels, respectively, for 5, 10, 15, 30, or 45 min (n=10 rats/group). Ten animals were untreated (control). The rats were killed after 2 or 30 days, and the maxillae were examined by light microscopy. Inflammation was evaluated through histomorphometric analysis with inflammatory cell count in the corona! and radicular thirds of the pulp. Fibroblasts were also counted. Scores were attributed to odontoblastic layer and vascular changes. Tertiary dentin area and pulp chamber central area were measured histomorphometrically. Data were compared by analysis of variance and Kruskal-Wallis test (p<0.05). Results: After 2 days, the amount of inflammatory cells increased in the coronal pulp occlusal third up to the 15-min application groups of each bleaching gel. In the groups exposed to each concentration for 30 and 45 min, the number of inflammatory cells decreased along with the appearance of necrotic areas. After 30 days, reduction on the pulp chamber central area and enlargement of the tertiary dentin area were observed, without the detection of inflammation areas. Conclusion: The rat model of extracoronal bleaching showed to be adequate for studies of bleaching protocols, as it was possible to observe alterations in the pulp tissues and tooth structure caused by different concentrations and application periods of bleaching agents.
Keywords: Bleaching agents; Animal models; Hydrogen peroxide